2004
DOI: 10.1007/s00125-004-1549-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on the severity of erectile dysfunction and response to treatment: analysis of data from tadalafil clinical trials

Abstract: Aims/hypothesis. A retrospective analysis of pooled data from twelve placebo-controlled trials was conducted to characterise the efficacy and safety of tadalafil for the treatment of erectile dysfunction in men with diabetes compared with that in men without diabetes. Methods. Patients were randomly allocated to tadalafil 10 mg, 20 mg, or placebo, taken as needed for 12 weeks. The study population comprised 637 men with diabetes (mean age 57 years) and 1681 men without diabetes (mean age 56 years). Results. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
105
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 35 publications
(32 reference statements)
16
105
1
4
Order By: Relevance
“…[1][2][3] Furthermore, individuals with diabetes may have other co-morbid conditions that are associated with ED without diabetes, such as renal failure, hypertension and chronic liver disease, making the precise association of diabetes with ED circumstantial under these conditions. On the other hand, our findings that EMP remain the sole predictor of ED in our diabetic subjects with ED, and the evidence that common risk factors, such as hyperlipidemia and hypertension, do not interfere with the association between EMP and ED suggest that EMP may be one important link between endothelial dysfunction and ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Furthermore, individuals with diabetes may have other co-morbid conditions that are associated with ED without diabetes, such as renal failure, hypertension and chronic liver disease, making the precise association of diabetes with ED circumstantial under these conditions. On the other hand, our findings that EMP remain the sole predictor of ED in our diabetic subjects with ED, and the evidence that common risk factors, such as hyperlipidemia and hypertension, do not interfere with the association between EMP and ED suggest that EMP may be one important link between endothelial dysfunction and ED.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The relative risk of ED increases with diabetes duration, poor glycemic control and the number of other complications present, including microvascular complications such as nephropathy, neuropathy and retinopathy, and macrovascular atherosclerosis. [1][2][3] One common denominator for these diseases is vascular endothelial dysfunction, and ED may be a marker for the potential development of vascular disease including myocardial infarction. [4][5][6] Vascular endothelium plays a pivotal role in pathogenesis of numerous thrombotic and inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…135 In separate trials, the ability of tadalafil to enhance erectile function in men with diabetes (predominantly type II) and ED was confirmed. 136,137 Despite the 637 men with diabetes having more severe ED than a group of 1681 men without diabetes, in the diabetic group, 53% of their attempts at intercourse were successful in the tadalafil group, compared with 22% in the placebo group. 137 Tadalafil, taken on demand, is also effective in the ED following bilateral nerve sparing radical retropubic prostatectomy.…”
Section: Clinical Trials With Tadalafilmentioning
confidence: 99%
“…136,137 Despite the 637 men with diabetes having more severe ED than a group of 1681 men without diabetes, in the diabetic group, 53% of their attempts at intercourse were successful in the tadalafil group, compared with 22% in the placebo group. 137 Tadalafil, taken on demand, is also effective in the ED following bilateral nerve sparing radical retropubic prostatectomy. 138 In combining 2102 men from 11 trials, with a broad spectrum of ED aetiology and various comorbid medical conditions, it was shown that tadalafil (10 or 20 mg) was effective in all subpopulations.…”
Section: Clinical Trials With Tadalafilmentioning
confidence: 99%
“…[5][6][7] Studies including patients with comorbid clinical conditions such as hyperlipidemia, hypertension and cardiovascular disease have also delineated the efficacy of tadalafil therapy. 5,8 In addition, numerous clinical trials have been conducted to evaluate response to therapy in various hard-to-treat populations of men with ED, for example, those with diabetes 9 and those who are post prostatectomy. 10 Clinically meaningful responses in these groups of patients have additionally helped to characterize the benefits of therapy.…”
Section: Introductionmentioning
confidence: 99%